Synthesis of clathrate cerium superhydride CeH9 at 80-100 GPa with atomic hydrogen sublattice - Salke, Nilesh P.; Davari Esfahani, M. Mahdi; Zhang, Youjun; Kruglov, Ivan A.; Zhou, Jianshi; Wang, Yaguo; Greenberg, Eran; Prakapenka, Vitali B.; Liu, Jin; Oganov, Artem R.; Lin, Jung-Fu (Nature communications, 2019)
Hydrogen-rich superhydrides are believed to be very promising high- T c superconductors. Recent experiments discovered superhydrides at very high pressures, e.g. FeH 5 at 130 GPa and LaH 10 at 170 GPa. With the motivation of discovering new hydrogen-rich high- T c superconductors at lowest possible pressure, here we report the prediction and experimental synthesis of cerium superhydride CeH 9 at 80–100 GPa in the laser-heated diamond anvil cell coupled with synchrotron X-ray diffraction. Ab initio calculations were carried out to evaluate the detailed chemistry of the Ce-H system and to understand the structure, stability and superconductivity of CeH 9 . CeH 9 crystallizes in a P6 3 /mmc clathrate structure with a very dense 3-dimensional atomic hydrogen sublattice at 100 GPa. These findings shed a significant light on the search for superhydrides in close similarity with atomic hydrogen within a feasible pressure range. Discovery of superhydride CeH 9 provides a practical platform to further investigate and understand conventional superconductivity in hydrogen rich superhydrides. Hydrogen-rich superhydrides are promising high-temperature superconductors which have been observed only at pressures above 170 GPa. Here the authors show that CeH 9 can be synthesized at 80-100 GPa with laser heating, and is characterized by a clathrate structure with a dense 3-dimensional atomic hydrogen sublattice.